Effect of cyclo-L-prolylglycine on pain response thresholds and morphine-induced analgesia in inbred BALB/c and C57Bl/6 mice - A. V. Nadorova; K. N. Koliasnikova; I. V. Chernyakova; L. G. Kolik (Фармакокинетика и Фармакодинамика, 2024)
Relevance. Cyclo-L-prolylglycine (CPG), discovered as an endogenous compound in the central nervous system, is involved in the formation of a reaction to emotional stress in rodents with a pronounced fear reaction and has an analgesic effect in vivo. However, data on the dependence of the antinociceptive effect of CPG on genotype are currently unavailable.Objective. To evaluate the effect of exogenous CPG on the thresholds of acute pain response and morphine–induced analgesia in mice with an opposite reaction to emotional stress.Methods. The experiments were performed on inbred male mice BALB/c (n = 207) and C57Bl/6 (n = 204). To assess the analgesic effect of CPG, the "writhing test" (0.75 % acetic acid solution, i.p.) and the "hot plate" (55 ± 0.5 °C).Results. CPG at doses of 1, 2, and 4 mg/kg, i.p., significantly reduced the number of writhings in BALB/c and C57Bl/6 mice, whereas the effect of CPG was comparable to that of diclofenac at a dose of 10 mg/kg per os. During thermal stimulation, interline differences in the antinociceptive effect of CPG were revealed, which was more pronounced at a maximum effective dose of 2 mg/kg in "stress-non-resistant" BALB/c mice compared with C57Bl/6 mice. CPG at a dose of 2 mg/kg weakened morphine-induced analgesia during thermal stimulation in BALB/c and C57Bl/6 mice for 30, 60, and 90 minutes of observation.Conclusion. The established dependence of the central antinociceptive effect of CPGs on genotype is important in the context of biomedical research on pain detection and control using pharmacological correctors.